UPAYA MENINGKATKAN KEMAMPUAN BELAJAR MATEMATIKA MELALUI MODEL PEMBELAJARAN TERBALIK (RECIPROCAL TEACHING) PADA SISWA KELAS XII IPS 1 SMA N 1 TAMBUSAI - Ermi Ermi (JURNAL PENDIDIKAN ROKANIA, 2021)
In today's modern era, many students are bored to learn in the classical way, especially in mathematics. Effective teaching must be able to create sufficient interest and motivation in students to excel, without creating stressful conditions, Slameto (2010). One type of learning strategy that provides opportunities for students to actively participate in learning and create a pleasant atmosphere in learning is learning by applying the learning strategy of the Reciprocal Teaching Learning Model. This learning model shows how direct learning can improve and influence student learning outcomes and is also a teaching procedure designed to teach students about cognitive strategies and help students understand the subject matter well. During the implementation of classroom action research which took place in 3 cycles in class XII IPS 1 SMA Negeri 1 Tambusai, it can be concluded, During the CAR, the Reciprocal Teaching Learning Model has been managed well. significant learning outcomes. In the first cycle, the score of students who reached the KKM was 51.72%. In the second cycle students who achieved the KKM 55.17% were completed, while in the third cycle students reached the KKM 75.86%. Thus the reverse learning model can improve students' mathematics learning outcomes, it is acceptable.